2001
DOI: 10.1007/s11864-001-0016-6
|View full text |Cite
|
Sign up to set email alerts
|

Advanced non-small cell lung cancer

Abstract: The treatment of advanced non-small cell lung cancer requires histologic proof of diagnosis, careful staging, and assessment of each patient's performance status and comorbidities. For patients with stage IIIB (pleural effusion) and stage IV disease who have a Cancer and Leukemia Group B performance status (PS) of 0 to 1, appropriate management consists of combination chemotherapy with a platinum (either cisplatin or carboplatin) combined with paclitaxel, gemcitabine, vinorelbine, docetaxel, or CPT-11. Dosages… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…[4] Of these comorbidities, bone pain is the most common, seen in 80% of patients with skeletal NSCLC metastases. [612] Other SREs such as fractures and hypercalcemia owe their pathophysiology primarily to the tumor-induced increase of osteoclast differentiation relative to osteoblasts. [811] Nevertheless, despite the prevalence of skeletal metastases—with the spine, ribs, and pelvis being the most common—encroachment upon the occipital condyle and atlas is exceedingly rare.…”
Section: Discussionmentioning
confidence: 99%
“…[4] Of these comorbidities, bone pain is the most common, seen in 80% of patients with skeletal NSCLC metastases. [612] Other SREs such as fractures and hypercalcemia owe their pathophysiology primarily to the tumor-induced increase of osteoclast differentiation relative to osteoblasts. [811] Nevertheless, despite the prevalence of skeletal metastases—with the spine, ribs, and pelvis being the most common—encroachment upon the occipital condyle and atlas is exceedingly rare.…”
Section: Discussionmentioning
confidence: 99%
“…• Studies have demonstrated clearly that chemotherapy has a benefit in survival rate and quality of life for patients with advanced NSCLC [16]. …”
Section: Whole Brain Radiotherapymentioning
confidence: 99%
“…The choice of a specific regimen is governed by other medical conditions, convenience, and economics. An overview of management for advanced NSCLC was recently published by Edelman and Khanwani [37]. Occasionally, a patient may present with a…”
Section: Serum Tumor Markersmentioning
confidence: 99%